Design and Performance Analysis of Dual-Axis Solar Tracking to Enhance PV Efficiency Using Mamdani Fuzzy Logic Method - Seflahir Dinata; Ahmad Faisal Mohamad Ayob; Fariq Alamsyahid Al Ghiffari; Didik Krisyanto; Heranudin Heranudin; Sunardi Sunardi (LPPM Universitas Andalas, 2026)
The efficiency of a solar panel (PV) depends on solar radiation. In general, the solar panels will produce maximum power with radiation of 1000 W/m2 at a temperature of 25 oC. The sun's relative position will affect the strength of solar radiation received by the PV. This work aims to implement Mamdani fuzzy logic to optimize sunlight detection by dual-axis solar tracking (DAST) movement. The designed solar tracker consists of a light sensor (light-dependent resistor/LDR) as the input, an Arduino Mega as the controller, and a linear actuator to drive the solar panels. The solar panels used are 100 Wp monocrystalline. Data collection was carried out for 10 hours with time intervals every 10 minutes, starting from 7.00 am to 17.00 pm. Efficiency optimization is reviewed by comparing the output voltage of solar panels using and without sunlight tracking. The test results show that the solar tracker shows significant performance in maximizing the capture of sunlight so that the PV gets optimum radiation. The energy generated by fixed and solar trackers is 0.63 kWh and 0.92 kWh, respectively. The solar tracker also result higher efficiency 4.17% more, it shows that the use of the proposed method can increase the PV efficiency.